Composite sulfide solid electrolyte and preparation method and application thereof
Patent Information
- Application Number
- CN202610960683.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-23
AI Technical Summary
其通过阴离子掺杂有效改善了离子电导率,但空气稳定性仍有明显不足
本发明提供一种复合硫化物固态电解质,采用晶格掺杂的硫化物固态电解质与长链烷基酸的复合,其中硫化物固态电解质通过硫位A元素掺杂,可有效提高硫化物电解质的空气稳定性,改善复合材料的均匀性;同时利用长链烷基酸的疏水性和低熔点特性及其渗透作用,可明显改进其空气稳定性,抑制锂枝晶,进一步改进复合硫化物固态电解质与正负极的界面稳定性;在特定的晶格掺杂硫化物固态电解质与长链烷基酸的共同作用下,获得优异的空气稳定性和离子电导率。
Smart Images

Figure CN122968408A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state battery technology, and in particular to a composite sulfide solid electrolyte, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries have been widely used in electric vehicles and large-scale energy storage due to their high energy density and long cycle life. However, currently, commercially available lithium-ion batteries mainly use liquid electrolytes, which are flammable, pose a risk of leakage, and are prone to thermal runaway, seriously threatening user safety. To improve the intrinsic safety of batteries, all-solid-state lithium batteries, which use non-flammable solid electrolytes instead of liquid electrolytes, are considered to be a promising next-generation electrochemical energy storage technology.
[0003] Sulfide-based electrolytes are among the most promising solid-state electrolytes due to their extremely high ionic conductivity. However, their practical application still faces significant challenges due to issues such as instability in air, high raw material costs, and instability at the positive and negative electrode interfaces. Because sulfide electrolytes readily absorb water and release toxic hydrogen sulfide gas in air, their powder preparation and film formation generally require an inert atmosphere, resulting in high processing costs. Although combining them with hydrophobic materials can alleviate air stability issues to some extent, problems such as uneven mixing, increased costs, and decreased ionic conductivity still exist. For example, patent application CN117673451A proposes a method for preparing anion-doped sulfide solid-state electrolytes by equimolarly substituting Li... 9.54 Si 1.74 P 1.44 S 11.7 X 0.3 Anion-doped sulfide solid electrolytes with S-sites in the internal lattice create vacancies by replacing larger ionic ions with smaller electronegativity, weakening the binding with lithium ions and providing a new pathway for ion transport. While anion doping effectively improves ionic conductivity, air stability remains significantly insufficient. Therefore, there is an urgent need to research a low-cost, easily fabricated hydrophobic sulfide electrolyte that simultaneously possesses high ionic conductivity and air stability. Summary of the Invention
[0004] The purpose of this invention is to overcome the defects and shortcomings of the prior art and provide a composite sulfide solid electrolyte that can improve ionic conductivity and effectively improve the air stability of the sulfide electrolyte.
[0005] Another object of the present invention is to provide a method for preparing a composite sulfide solid electrolyte.
[0006] Another objective of this invention is to provide an application of a composite sulfide solid electrolyte in solid-state lithium batteries.
[0007] Another object of the present invention is to provide a solid-state lithium battery.
[0008] The above-mentioned objective of this invention is achieved through the following technical solution: The present invention provides a composite sulfide solid electrolyte, comprising a sulfide electrolyte and a C13-C20 long-chain alkyl acid melt-permeated inside the sulfide electrolyte, wherein the mass ratio of the sulfide electrolyte to the C13-C20 long-chain alkyl acid is 100:(0.1-5). The molecular formula of the sulfide electrolyte is Li 6-x PS 5-x-y A y B 1+x In the formula, A is selected from at least one of O, Se, and Te, and B is selected from at least one of Cl, Br, or I, wherein O <x≤0.7,0<y≤1.5。
[0009] The composite sulfide solid electrolyte of this invention achieves excellent air stability and ionic conductivity by controlling the lattice doping of the sulfide and its interaction with long-chain alkyl acids that permeate hydrophobically. Specifically, doping the S-site of the sulfide electrolyte with alumina improves its air stability. Furthermore, by combining the sulfide electrolyte with long-chain alkyl acids that possess low melting points and high permeability, the high hydrophobicity of the long-chain alkyl acids significantly improves its air stability. Additionally, the electronic insulation properties of the long-chain alkyl acids suppress lithium dendrite formation, thereby enhancing structural stability.
[0010] It should be noted that the content of A needs to be controlled in this invention. Increasing the amount of A doping is beneficial to improving air stability, and an appropriate amount of A doping can improve ionic conductivity. However, excessive A doping will reduce ionic conductivity, and excessive A doping has a limited effect on improving air stability.
[0011] In some implementations, 0.3 ≤ x ≤ 0.6, 0.1 ≤ y ≤ 0.7.
[0012] In some embodiments, A is selected from at least two of O, Se, and Te, and B is selected from at least two of Cl, Br, or I.
[0013] In some embodiments, the sulfide electrolyte has the molecular formula Li. 6-x PS 5-x-y A 1 a O b B 1 c B 2 d The A 1 B is independently selected from either Se or Te. 1 B2 The solution is independently selected from Cl, Br, or I, and a+b=y, c+d=1+x; that is, 0.1≤a+b≤0.7, 1.3≤c+d≤1.6.
[0014] In the sulfide electrolyte, when O is present at site A, the binding force between the long-chain alkyl acid and the sulfide electrolyte can be improved through hydrogen bonding between hydrogen ions in the long-chain alkyl acid and oxygen ions in the sulfide electrolyte, thus improving the dispersibility of the long-chain alkyl acid and further enhancing air stability. However, the O content needs to be controlled, as excessive O doping will reduce ionic conductivity. Furthermore, this invention has found that when B contains multiple halogen elements, it is even more beneficial to improve air stability and ionic conductivity.
[0015] In some implementations, 0.1≤a≤0.9, 0.1≤b≤0.3, 0.8≤c≤1, and 0.1≤d≤0.7.
[0016] In some embodiments, the C13-C20 long-chain alkyl acid is selected from saturated long-chain fatty acids and / or long-chain alkylphosphonic acids; Preferably, the long-chain fatty acid has the molecular formula C1. n H 2n+1 COOH, where 13≤n≤20; Preferably, the long-chain alkylphosphonic acid has the molecular formula C0. n H 2n+1 PO(OH)2, where 13≤n≤18.
[0017] This long-chain alkylphosphonic acid is in a solid state and has a low melting point (≤100℃), which facilitates its composite with sulfide electrolytes through melt infiltration. Its long-chain alkyl structure exhibits excellent hydrophobicity, improving the air stability of the sulfide electrolyte. However, the content of the long-chain alkyl acid should be carefully monitored; excessive amounts will reduce the ionic conductivity of the composite solid electrolyte. Furthermore, the long-chain alkyl acid possesses electronic insulating properties, which can suppress lithium dendrite formation.
[0018] In some embodiments, the mass ratio of the sulfide electrolyte to the C13-C20 long-chain alkyl acid is 100:(0.4-2.6).
[0019] In some embodiments, the ionic conductivity of the composite sulfide solid electrolyte is 5.8 × 10⁻⁶. -3 S / cm~9.5×10 -3 S / cm.
[0020] This invention provides a method for preparing a composite sulfide solid electrolyte, comprising the following steps: S1, mix the precursor raw materials of each stoichiometric ratio, ball mill, and heat treat at 450-550℃ for 5-20h under an inert atmosphere to obtain sulfide solid electrolyte. S2, the sulfide electrolyte is mixed with C13-C20 long-chain alkyl acid, and heated to above the melting point of the C13-C20 long-chain alkyl acid for melt infiltration treatment to obtain a composite sulfide solid electrolyte.
[0021] In some embodiments, in step S1, the precursor raw material is selected from LiB, Li2S, Li2A and P2S5; wherein A is selected from O, Se and Te, and B is selected from Cl, Br and I.
[0022] In some embodiments, in step S1, the rotational speed of the ball mill is 300~600 rpm.
[0023] In some embodiments, in step S2, the ball mill rotates at a speed of 300-600 rpm, the ball milling atmosphere is an inert atmosphere, and the ball milling time is 5-20 hours.
[0024] This invention provides an application of a composite sulfide solid electrolyte in solid-state lithium batteries.
[0025] The present invention provides a solid-state lithium battery, comprising a positive electrode, a negative electrode and the aforementioned composite sulfide solid electrolyte.
[0026] Compared with the prior art, the beneficial effects of the present invention are: This invention provides a composite sulfide solid electrolyte, which is a composite of a lattice-doped sulfide solid electrolyte and a long-chain alkyl acid. The sulfide solid electrolyte is doped with sulfur-site A element, which can effectively improve the air stability of the sulfide solid electrolyte and improve the uniformity of the composite material. At the same time, the hydrophobicity and low melting point of the long-chain alkyl acid and its permeation effect can significantly improve its air stability, suppress lithium dendrites, and further improve the interfacial stability between the composite sulfide solid electrolyte and the positive and negative electrodes. Under the combined effect of the specific lattice-doped sulfide solid electrolyte and the long-chain alkyl acid, excellent air stability and ionic conductivity are obtained. Attached Figure Description
[0027] Figure 1 The image shows the electrochemical impedance spectroscopy of the composite sulfide solid electrolyte prepared in Example 1; where Z' refers to the real impedance and -Z'' refers to the negative imaginary impedance.
[0028] Figure 2 The image shows the electrochemical impedance spectroscopy of the solid electrolyte prepared in Comparative Example 1; where Z' refers to the real impedance and -Z'' refers to the negative imaginary impedance.
[0029] Figure 3The graph shows the amount of hydrogen sulfide evolution over time in the composite sulfide solid electrolyte prepared in Example 1.
[0030] Figure 4 The graph shows the amount of hydrogen sulfide evolution over time for the solid electrolyte prepared in Comparative Example 1. Detailed Implementation
[0031] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0032] Example 1 A composite sulfide solid electrolyte, comprising a sulfide electrolyte and a long-chain alkyl acid; The molecular formula of the sulfide electrolyte is Li. 5.5 PS 4.1 Se 0.3 O 0.1 Cl 0.9 Br 0.6 The long-chain alkyl acid is selected from C 17 H 35 The weight ratio of COOH, sulfide electrolyte, and long-chain alkyl acid is 100:1.
[0033] The preparation method of the composite sulfide solid electrolyte includes the following steps: S1, using LiCl, LiBr, Li2S, Li2Se, Li2O and P2S5 as precursors, was mixed in a molar ratio of 0.9:0.6:1.6:0.3:0.1:0.5, ball-milled at 450 rpm for 12 h under an argon atmosphere, and then heat-treated at 500 °C for 12 h under an argon atmosphere to obtain a sulfide solid electrolyte. S2, the sulfide electrolyte is reacted with a long-chain alkyl acid (C 17 H 35 The mixture (COOH) is heated to above the melting point of the long-chain alkyl acid to undergo melt infiltration treatment, thereby obtaining a composite sulfide solid electrolyte.
[0034] Example 2 A composite sulfide solid electrolyte, comprising a sulfide electrolyte and a long-chain alkyl acid; The molecular formula of the sulfide electrolyte is Li. 5.5 PS 4.1 Te 0.3 O 0.1 ClBr 0.5 The long-chain alkyl acid is selected from C 18 H 37The weight ratio of PO(OH)2, sulfide electrolyte, and long-chain alkyl acid is 100:1.
[0035] The preparation method of the composite sulfide solid electrolyte includes the following steps: S1, using LiCl, LiBr, Li2S, Li2Te, Li2O and P2S5 as precursors, was mixed in a molar ratio of 1.0:0.5:1.6:0.3:0.1:0.5, ball-milled at 450 rpm for 12 h in an argon atmosphere, and then heat-treated at 500 °C for 12 h in an argon atmosphere to obtain a sulfide solid electrolyte. S2, the sulfide electrolyte is reacted with a long-chain alkyl acid (C 18 H 37 The mixture is PO(OH)2 and heated to above the melting point of the long-chain alkyl acid for melt infiltration treatment to obtain a composite sulfide solid electrolyte.
[0036] Example 3 A composite sulfide solid electrolyte, comprising a sulfide electrolyte and a long-chain alkyl acid; The molecular formula of the sulfide electrolyte is Li. 5.5 PS 4.1 Se 0.3 O 0.1 ClI 0.5 The long-chain alkyl acid is selected from C 18 H 37 The weight ratio of PO(OH)2, sulfide electrolyte, and long-chain alkyl acid is 100:1.
[0037] The preparation method of the composite sulfide solid electrolyte includes the following steps: S1, using LiCl, LiI, Li2S, Li2Se, Li2O and P2S5 as precursors, was mixed in a molar ratio of 1.0:0.5:1.6:0.3:0.1:0.5, ball-milled for 12 h at 450 rpm under an argon atmosphere, and then heat-treated for 12 h at 500 °C under an argon atmosphere to obtain a sulfide solid electrolyte. S2, the sulfide electrolyte is reacted with a long-chain alkyl acid (C 18 H 37 The mixture is PO(OH)2 and heated to above the melting point of the long-chain alkyl acid for melt infiltration treatment to obtain a composite sulfide solid electrolyte.
[0038] Examples 4-16 and Comparative Examples 1-9 A series of composite sulfide solid electrolytes are provided, which differ from Example 1 in that the weight ratios of the sulfide electrolyte, long-chain alkyl acid, and sulfide electrolyte to long-chain alkyl acid in this example or comparative example are shown in Table 1.
[0039] The preparation method of the composite sulfide solid electrolyte includes the following steps: S1, mix the precursor raw materials of the stoichiometric meter, ball mill for 12 h at 450 rpm under argon atmosphere, and then heat treat for 12 h at 500 °C under argon atmosphere to obtain sulfide solid electrolyte. The precursor raw materials are selected from Li2S, P2S5, Li2O, Li2Se, Li2Te, LiCl, LiBr and LiI.
[0040] S2, the sulfide electrolyte is mixed with a long-chain alkyl acid and heated to above the melting point of the long-chain alkyl acid for melt infiltration treatment to obtain a composite sulfide solid electrolyte.
[0041] Table 1
[0042] In Comparative Examples 1 and 3-4, when the sulfide solid electrolyte does not contain long-chain alkyl acids, its preparation method includes the following steps: mixing the precursor raw materials in stoichiometric proportions, ball milling for 12 hours at 450 rpm under an argon atmosphere, and then heat-treating for 12 hours at 500°C under an argon atmosphere to obtain the sulfide solid electrolyte; the precursor raw materials are selected from Li2S, P2S5, Li2O, Li2Se, Li2Te, LiCl, LiBr and LiI.
[0043] The performance test method is as follows: 1. Test method for ionic conductivity: Weigh 100 mg of electrolyte into a mold in a glove box, then pressurize it at 360 MPa for 3 minutes. Analyze the conductivity using an AC impedance method (frequency range 10). -2 ~10 5 The overall impedance of the sulfide solid electrolyte layer was measured at Hz (with a bias voltage of 5 mV), and the ionic conductivity was calculated using the formula σ = L / R × S. Where σ is the ionic conductivity (S / cm). –1 L is the thickness of the sulfide solid electrolyte layer (cm), R is the total impedance of the sulfide solid electrolyte layer (Ω), and S is the area of the solid electrolyte layer (cm²). 2 ).
[0044] The electrochemical impedance spectra of the solid electrolytes in Example 1 and Comparative Example 1 are as follows: Figure 1-2 As shown.
[0045] 2. Ionic conductivity retention rate: After being exposed to air with a relative humidity of 40% for 30 minutes, the ionic conductivity retention rate was measured and calculated using the above-mentioned ionic conductivity test method.
[0046] 3. Hydrogen sulfide precipitation: Weigh 25 mg of sulfide-based solid electrolyte in a glove box, seal it, and transfer it to a 15L glass container. Place the hydrogen sulfide sensor and fan in the glass container. Before testing, remove the sealing layer, start the hydrogen sulfide gas sensor, turn on the fan, and then quickly close the lid to create a sealed atmosphere. Read the amount of hydrogen sulfide precipitation from the hydrogen sulfide gas sensor and record the change in hydrogen sulfide precipitation over time.
[0047] In Example 1 and Comparative Example 1, the amount of hydrogen sulfide evolved by the solid electrolyte over time is as follows: Figure 3-4 As shown.
[0048] The results show that the composite sulfide solid electrolyte of the present invention has excellent ionic conductivity and air stability, with an ionic conductivity ≥ 5.8 × 10⁻⁶. -3 S / cm, ionic conductivity retention rate ≥80% after 30 min of exposure to air, hydrogen sulfide emission ≤9.1ppm, and when element A and / or element B are multi-site doped, it has higher air stability and ionic conductivity.
[0049] Compared with Example 1, Comparative Example 1, which does not contain long-chain alkyl acids, has a lower retention rate of ionic conductivity, excessive hydrogen sulfide evolution, and poor air stability.
[0050] As can be seen from Comparative Examples 2-4, typical sulfide solid electrolytes (Li) 5.5 PS 4.5 Cl 1.5 It has the defect of extremely poor air stability. Doping with multiple halogen elements and introducing long-chain alkyl acids can improve air stability.
[0051] Comparative Example 5 shows that when a sulfide solid electrolyte is combined with a long-chain alkyl acid and the amount of B-site element doping in the sulfide solid electrolyte is insufficient, the ionic conductivity will decrease.
[0052] As can be seen from Comparative Example 6, when the sulfide solid electrolyte is combined with long-chain alkyl acid and the amount of A-site element doping in the sulfide solid electrolyte is excessive, it has little effect on air stability, but it will lead to a significant decrease in ionic conductivity.
[0053] As can be seen from Comparative Examples 7-8, the carbon chain length of the long-chain alkyl acid needs to be controlled within a suitable range to achieve both ionic conductivity and air stability. When the carbon chain of the long-chain alkyl acid is too short, the hydrophobicity of the long-chain alkyl structure is insufficient, resulting in poor air stability of the sulfide solid electrolyte. When the carbon chain of the long-chain alkyl acid is too long, it will reduce the ionic conductivity of the composite solid electrolyte.
[0054] As can be seen from Comparative Example 9, when the content of long-chain alkyl acids is too high, it will lead to a decrease in the ionic conductivity of the composite solid electrolyte.
[0055] The above embodiments of the present invention are merely examples for clearly illustrating the present invention and are not intended to limit the implementation of the present invention. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all possible implementations here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A composite sulfide solid electrolyte, characterized in that, It includes a sulfide electrolyte and C13-C20 long-chain alkyl acids that are melt-permeated inside the sulfide electrolyte, and the mass ratio of the sulfide electrolyte to the C13-C20 long-chain alkyl acids is 100:(0.1-5). The molecular formula of the sulfide electrolyte is Li 6-x PS 5-x-y A y B 1+x In the formula, A is selected from at least one of O, Se, and Te, and B is selected from at least one of Cl, Br, or I, wherein O <x≤0.7,0<y≤1.5。 2. The composite sulfide solid electrolyte according to claim 1, characterized in that, 0.3≤x≤0.6, 0.1≤y≤0.
7.
3. The composite sulfide solid electrolyte according to claim 1 or 2, characterized in that, The molecular formula of the sulfide electrolyte is Li 6-x PS 5-x-y A 1 a O b B 1 c B 2 d The A 1 B is independently selected from either Se or Te. 1 B 2 Choose independently from Cl, Br, or I, and a+b=y, c+d=1+x.
4. The composite sulfide solid electrolyte according to claim 3, characterized in that, 0.1≤a≤0.9, 0.1≤b≤0.3, 0.8≤c≤1, 0.1≤d≤0.
7.
5. The composite sulfide solid electrolyte according to claim 1, characterized in that, The C13-C20 long-chain alkyl acid is selected from long-chain fatty acids and / or long-chain alkylphosphonic acids; The molecular formula of the long-chain fatty acid is C1 n H 2n+1 COOH, where 13≤n≤20; The molecular formula of the long-chain alkylphosphonic acid is C0 n H 2n+1 PO(OH)2, where 13≤n≤18.
6. The composite sulfide solid electrolyte according to claim 1, characterized in that, The mass ratio of the sulfide electrolyte to the C13-C20 long-chain alkyl acid is 100:(0.4-2.6).
7. The composite sulfide solid electrolyte according to claim 1, characterized in that, The ionic conductivity of the composite sulfide solid electrolyte is 5.8 × 10⁻⁶. -3 S / cm~9.5×10 -3 S / cm.
8. A method for preparing the composite sulfide solid electrolyte according to any one of claims 1-7, characterized in that, Includes the following steps: S1, mix the precursor raw materials of each stoichiometric ratio, ball mill, and heat treat at 450-550℃ for 5-20h under an inert atmosphere to obtain sulfide solid electrolyte. S2, the sulfide solid electrolyte is mixed with C13-C20 long-chain alkyl acid, and heated to above the melting point of the C13-C20 long-chain alkyl acid for melt infiltration treatment to obtain composite sulfide solid electrolyte.
9. The application of the composite sulfide solid electrolyte according to any one of claims 1-7 in a solid-state lithium battery.
10. A solid-state lithium battery, characterized in that, It includes a positive electrode, a negative electrode, and a composite sulfide solid electrolyte as described in any one of claims 1-7.
Citation Information
Patent Citations
Preparation method of anion-doped sulfide solid electrolyte
CN117673451A